Design of a novel curcumin-soybean phosphatidylcholine complex-based targeted drug delivery systems. (1st January 2017) - Xie, Jiajiang; Li, Yanxiu; Song, Liang; Pan, Zhou; Ye, Shefang; Hou, Zhenqing
Abstract: Recently, the global trend in the field of nanomedicine has been toward the design of combination of nature active constituents and phospholipid (PC) to form a therapeutic drug-phospholipid complex. As a particular amphiphilic molecular complex, it can be a unique bridge of traditional dosage-form and novel drug delivery system. In thisarticle, on the basis of drug-phospholipid complex technique and self-assembly technique, we chose a pharmacologically safe and low toxic drug curcumin (CUR) to increase drug-loading ability, achieve controlled/sustained drug release and improve anticancer activity. A novel CUR-soybean phosphatidylcholine (SPC) complex and CUR-SPC complex self-assembled nanoparticles (CUR-SPC NPs) were prepared by a co-solvent method and a nanoprecipitation method. DSPE-PEG-FA was further functionalized on the surface of PEG-CUR-SPC NPs (designed as FA-PEG-CUR-SPC NPs) to specifically increase cellular uptake and targetability. The FA-PEG-CUR-SPC NPs showed a spherical shape, a mean diameter of about 180 nm, an excellent physiological stability and pH-triggered drug release. The drug entrapment efficiency and drug-loading content was up to 92.5 and 16.3%, respectively. In vitro cellular uptake and cytotoxicity studies demonstrated that FA-PEG-CUR-SPC NPs and CUR-SPC NPs presented significantly stronger cellular uptake efficacy and anticancer activity against HeLa cells and Caco-2 cells compared to free CUR, CUR-SPC NPs and PEG-CUR-SPC NPs. More importantly, FA-PEG-CUR-SPC NPs showed the prolonged systemic circulation lifetime and enhanced tumor accumulation compared with free CUR and PEG-CUR-SPC NPs. These results suggest that the FA targeted PEGylated CUR-SPC complex self-assembled NPs might be a promising candidate in cancer therapy.